Infigratinib in upper tract urothelial carcinoma versus urothelial carcinoma of the bladder and its association with comprehensive genomic profiling and/or cell‐free DNA results. Issue 11 (24th March 2020) - Pal, Sumanta K.; Bajorin, Dean; Dizman, Nazli; Hoffman‐Censits, Jean; Quinn, David I.; Petrylak, Daniel P.; Galsky, Matthew D.; Vaishampayan, Ulka; De Giorgi, Ugo; Gupta, Sumati; Burris, Howard A.; Soifer, Harris S.; et al.
Abstract : Background: Infigratinib (BGJ398) is a potent and selective fibroblast grown factor receptor 1 to 3 (FGFR1‐3) inhibitor with significant activity in patients with advanced or metastatic urothelial carcinoma bearing FGFR3 alterations. Given the distinct biologic characteristics of upper tract urothelial carcinoma (UTUC) and urothelial carcinoma of the bladder (UCB), the authors examined whether infigratinib had varying activity in these settings. Methods: Eligible patients had metastatic urothelial carcinoma with activating FGFR3 mutations and/or fusions. Comprehensive genomic profiling was performed on formalin‐fixed, paraffin‐embedded tissues. Blood was collected for cell‐free DNA analysis using a 600‐gene panel. Patients received infigratinib at a dose of 125 mg orally daily (3 weeks on/1 week off) until disease progression or intolerable toxicity occurred. The overall response rate (ORR; partial response [PR] plus complete response [CR]) and disease control rate (DCR; CR plus PR plus stable disease [SD]) were characterized. Results: A total of 67 patients were enrolled; the majority (70.1%) had received ≥2 prior antineoplastic therapies. In 8 patients with UTUC, 1 CR and 3 PRs were observed (ORR, 50%); the remaining patients achieved a best response of SD (DCR, 100%). In patients with UCB, 13 PRs were observed (ORR, 22%), and 22 patients had a best response of SD (DCR, 59.3%). Notable differences in genomic alterations between patients with UTUC and those with UCB included higher frequencies of FGFR3‐TACC3 fusions (12.5% vs 6.8%) and FGFR3 R248C mutations (50% vs 11.9%), and a lower frequency of FGFR3 S249C mutations (37.5% vs 59.3%). Conclusions: Differences in the cumulative genomic profile were observed between patients with UTUC and those with UCB in the current FGFR3 ‐restricted experience, underscoring the distinct biology of these diseases. These results support a planned phase 3 adjuvant study predominantly performed in this population. Abstract : Infigratinib demonstrates activity in patients with metastatic urothelial carcinoma (UC) bearing fibroblast growth factor receptor 3 ( FGFR3 ) mutations and/or fusions, with particular activity noted in patients with upper tract UC (UTUC). Key differences in FGFR3 alterations are noted between UTUC and UC of the bladder in the genomically selected patients in the current study.